Instytut Zachodni - wielkopolski ośrodek myśli politycznej - Pospieszalski, Karol Marian (Wydział Prawa i Administracji UAM, 1992)
The author, one of the first employees of Western Institute in Poznań, presents a history of rise of this scientific institution under the German occupation, its history in the People's Republic period and its present state, as well as its scientific output in the field of research on German politics, economic and cultural neighbourhood and - presently - on the problems of integration, especially of Western Polish territories with West European countries.
Western Institute - Wielkopolska center of political thought